2021
DOI: 10.3390/cells10040960
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Resident and Recruited Macrophages in Primary Tumor and Metastatic Microenvironments: Potential Targets in Cancer Therapy

Abstract: Macrophages within solid tumors and metastatic sites are heterogenous populations with different developmental origins and substantially contribute to tumor progression. A number of tumor-promoting phenotypes associated with both tumor- and metastasis-associated macrophages are similar to innate programs of embryonic-derived tissue-resident macrophages. In contrast to recruited macrophages originating from marrow precursors, tissue-resident macrophages are seeded before birth and function to coordinate tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 258 publications
(353 reference statements)
0
27
0
Order By: Relevance
“…Consequently the number of TAMs is associated with a poor prognosis for several types of cancer (44,(111)(112)(113)(114). TAMs can originate from tissue resident macrophages or from circulating monocytes that infiltrate the tumor (115). How TAMs acquire this pro-tumorigenic phenotype is still largely unknown, but several studies have shown that their migration and immunesuppressive activity can be greatly affected by the composition and mechanical properties of the surrounding ECM, and in particular by collagen (86,(116)(117)(118).…”
Section: Collagen-mediated Modulation Of Macrophage Activitymentioning
confidence: 99%
“…Consequently the number of TAMs is associated with a poor prognosis for several types of cancer (44,(111)(112)(113)(114). TAMs can originate from tissue resident macrophages or from circulating monocytes that infiltrate the tumor (115). How TAMs acquire this pro-tumorigenic phenotype is still largely unknown, but several studies have shown that their migration and immunesuppressive activity can be greatly affected by the composition and mechanical properties of the surrounding ECM, and in particular by collagen (86,(116)(117)(118).…”
Section: Collagen-mediated Modulation Of Macrophage Activitymentioning
confidence: 99%
“…Depleting or stabilizing MCs has been hypothesized to enhance anti-cancer mechanisms ( 76 ). As with MCs, it was hypothesized tumor macrophage depletion and/or inhibition was also a plausible strategy for anti-cancer therapeutics ( 77 ). Now, macrophages are at the forefront of translational ACT research and are poised to become another cell in the arsenal of cancer cell immunotherapies ( 78 ).…”
Section: Discussionmentioning
confidence: 99%
“… 29 , 30 , 31 , 32 Obviously, these macrophages are one of the earliest cells interacting with transformed cells in the process of tumor formation. 33 Monocyte-derived TAMs originate from circulating monocytes in the peripheral circulation. In response to the internal environment after tumor formation, these cells are recruited to the TME and rapidly differentiate into macrophages.…”
Section: Macrophages In Tumorsmentioning
confidence: 99%